Bryophyllum pinnatum in the treatment of restless legs syndrome: A case series documented with polysomnography - von Manitius, Sigrid (Clin Case Rep, 2019)
Restless legs syndrome may seriously affect patients' sleep and quality of life, but established pharmacological therapy can often have severe side effects. Therefore, new therapeutic approaches such as well‐tolerated preparations from the medicinal plant Bryophyllum pinnatum should be considered as alternatives. Their sedative and spasmolytic properties might contribute to improve patients' condition.